The Relationship between Intrinsic Motivation and Student Academic Procrastination in the Islamic Religious Education Learning System (Case Study : Kadiri University Student) - Titin Widya Risni; Pamadya Vitasmoro (Journal of Islamic Education Research, 2023)
This study seeks the relationship of intrinsic motivation and academic procrastination with learning systems. The research phase began with the distribution of questionnaires to 40 students who participated in Islamic religious education learning. The test performed is a chi-square with a contingency of 2 x 2. The findings obtained were the relationship between intrinsic motivation and the learning system of 8.496 with a significant of 0.048 < 0.05 using an intrinsic motivation improvement strategy with an intense communication model for student complaints and tasks given. Efforts to relationship academic procrastination with the learning system amounted to 4.273 with a significant of 0.047 < 0.05 using intrinsic motivation strategies in the form of value benefits, project assignments had the opportunity to participate in scientific work and discussion of student complaints.